Error Analysis of Using Simple Past Tense in Writing Sentences at the Third Semester of English Language Education Program in University of Batanghari - Atarigsyah, Muhamad; Fitri, Nurul; Silfia, Efa (JELT: Journal of English Language Teaching, 2024)
This research investigates the errors made by third-semester students in the English Language Education Program at the University of Batanghari when using Simple Past Tense. The research aims to identify the types of errors based on Dulay et al.'s Surface Strategy taxonomy and explore the causes of errors. The research used a Descriptive Qualitative design. Research instruments included a writing test and documentation of test results. The findings revealed that students made various errors in using Simple Past Tense, with the error of omission constituting 57 error items (26.6%), error of addition constituting 37 items (16.6%), the error of misformation constituting 123 items (55.2%), and error of misordering constituting 6 items (1,6%) of total errors. The total of errors is 223 error items. The most recurring error is misformation, while misordering is the least common. The causes of errors are identified as overgeneralization, insufficient grammatical knowledge, and insufficient vocabulary knowledge.Keywords: Error analysis, simple past tense, surface strategy taxonomy